Multimodality Imaging of Cardiac Transthyretin Amyloidosis 16 Years After a Domino Liver Transplantation. Issue 7 (17th March 2016) - Bechiri, M. Y.; Eliahou, L.; Rouzet, F.; Fouret, P.‐J.; Antonini, T.; Samuel, D.; Adam, R.; Adams, D.; Slama, M. S.; Algalarrondo, V.
Abstract : We report the case of a 62‐year‐old man hospitalized in May 2015 for symptomatic heart failure. His medical history included two liver transplantations. The first liver transplantation was performed in 1999 for a mixed alcoholic and hepatitis C–related cirrhosis and the patient received the liver of another patient with Val30Met transthyretin amyloidosis using the domino technique. In 2008, he complained of neuropathic pains and an iatrogenic‐acquired transthyretin amyloidosis was diagnosed. On cardiac evaluation, amyloidosis was suspected. In March 2010, a second liver transplantation was performed with a deceased donor without complication. In May 2015, a first episode of symptomatic heart failure occurred and cardiac amyloidosis was investigated by a multimodality evaluation. Electrocardiogram, cardiac biomarkers, echocardiography, and cardiac MRI were in favor of the diagnosis of amyloidosis, whereas 99m Tc‐dicarboxypropane diphosphonate scintigraphy was not. Endomyocardial biopsy finally confirmed the positive diagnosis of iatrogenic‐acquired cardiac amyloidosis. This case is, to the best of our knowledge, the first to report biopsy‐proven cardiac amyloidosis induced by domino liver transplantation and progressing heart failure in spite of retransplantation. The diagnostic modalities are discussed. This case should alert physicians to the cardiac risk in domino liver transplanted patients. Abstract : This article reports the case of a patient with biopsy‐proven cardiac transthyretin amyloidosis and heart failure secondary to a domino liver transplantation.